Failure-proof spatio-temporal composition of sensor cloud services - Neiat, A.; Bouguettaya, A.; Sellis, T.; Dong, Hai (Springer Verlag, 2014)
We propose a new failure-proof composition model for Sensor-Cloud services based on dynamic features such as spatio-temporal aspects. To evaluate Sensor-Cloud services, a novel spatio-temporal quality model is introduced. We present a new failure-proof composition algorithm based on D* Lite to handle QoS changes of Sensor-Cloud services at run-time. Analytical and simulation results are presented to show the performance of the proposed approach.